Pengunaan Trichoderma sp Pada Poliembrioni Benih Jeruk Siam Madu (Citrus nobillis L) - Habel, Milka Alvionita; Wanget, Sesilia A.; Sumayku, Betrje R.A. (AGRI-SOSIOEKONOMI, 2024)
This study aims to determine the effect of using Trichoderma sp on polyembryony of honey Siamese orange seeds. This research was conducted at the Plant and Environment Laboratory, Sub-Laboratory of Genetics and Plant Breeding, Faculty of Agriculture, Sam Ratulangi University, Manado. The design of this study used a completely randomized design (CRD) with 2 factors, namely the concentration of trichoderma sp. T1 (109), T2 (108), T3 (107) and immersion time, W1 (24 hours), W2 (16 hours), W3 (8 hours). The variables observed were: Germination Power (Viability), Polyembryony, Root Weight. The results of the research showed that Trichoderma sp at a dose of 108 and a soaking time of 8 hours obtained the highest germination of Siam Honey orange seeds. From the results of the polyembryony research on honey Siamese orange seeds using Trichoderma sp, 40% polyembryony was obtained, whereas polyembryonic growth on honey Siamese orange seeds without Trichoderma sp obtained 16,6% polyembryony.